Assessment of knowledge, attitude, and practice of pharmacovigilance amongst undergraduate students at a tertiary care teaching hospital: a questionnaire-based study - Barad, Hiral H.; Hingorani, Sadhana K.; Banzal, Neeta (International Journal of Basic & Clinical Pharmacology, 2024)
Background: Pharmacovigilance ensures patient safety and rational medication use. Spontaneous reporting by healthcare professionals is crucial, but underreporting is a major limitation. Education and training are vital to improve Adverse Drug Reaction (ADR) reporting. Inculcating pharmacovigilance into undergraduate programs empowers medical students to report ADRs. Methods: This prospective questionnaire-based study focused on assessing knowledge, attitude, and practice (KAP) regarding pharmacovigilance. A total of 223 medical undergraduate students of which 156 were students in 2nd year and 67 in 3rd final years who gave their consent were included in this study. Participants completed a pre-questionnaire before undergoing a training session on pharmacovigilance related to KAP. Following the training session, a post-questionnaire was given. Pre- and post-test questionnaires were compared and analysed using an appropriate statistical test. Results: The study showed that knowledge and attitude scores among second and third-year medical students improved after the training program. Following training, the mean knowledge score for second-year students significantly increased from 5.56 to 8.6, while their mean attitude score increased from 5.9 to 7.24. Similarly, for third-final-year students, the mean knowledge score improved from 6.62 to 9.01, and the mean attitude score increased from 6.69 to 7.52. The results clearly showed that the training program had a positive impact on the knowledge and attitude of both student groups. The mean practice scores for second-year and third-final-year students were 0.76 and 1.34, respectively. Conclusions: The study showed significant improvement in knowledge and attitude after the educational intervention, indicating a positive impact of the training program.